FEMALE FIGURES IN THE UKRAINIAN WAR OF INDEPENDENCE 1917 – 1921 IN EXILE: WORK FOR THE FUTURE OF UKRAINE - VLASOVA , Viktoriia; POLIAKOVA , Larysa (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the article is to reveal the information potential of the memoir heritage of the Ukrainian War of Independence 1917 – 1921 heroines for understanding their contribution to the Ukrainian cause abroad. Using the memories of these women, we can analyze their situation after the defeat of the Ukrainian–Soviet War, and determine exactly how they made their daily life in other countries. Also, the purpose of the article is to identify the success they achieved in the fields of their own professional activity, overcoming the difficulties of emigration. The research methodology is based on general scientific methods of analysis, synthesis, generalization. To analyze the sources of personal origin, the method of critical discourse analysis has been used. The method of sociological science, specifically biographical, has been also used. The study is based on a feminist and gender approach. The scientific novelty of the article consists in the following: for the first time there has been analyzed insufficiently studied aspect of the period of the Ukrainian War of Independence 1917 – 1921, particularly the contribution of women activists to the continuation of the Ukrainian issue in other countries. There have been found patterns, similarities and differences in the experience of female figures of the national liberation process who emigrated to different countries and continents. Based on the memoir heritage, for the first time there have been revealed and systematized the personal challenges that these women faced overseas. We have analyzed the way they overcame those complexities, what they did useful for the case of the Ukrainian state, and how they were implemented to their own professional activities. The Conclusion. The research is a promising area of studying aspects of the Ukrainian War of Independence 1917 – 1921. The collected facts about forced moving abroad from the memoirs of women participants in the national liberation process show their varied experiences, but also common features. The research shows that women continued their activities in favour of Ukraine after the rout in the Independence War, overcoming emigration complications and hoping for the revival of the state. The analysis of their contribution to this affair and highlighting their professional activities will enrich the study of the Ukrainian national liberation process 1917 – 1921. Key words: Ukrainian War of Independence 1917 – 1921, Soviet-Ukrainian War, women's history, emigration, Ukrainian People's Republic, Second Hetmanate, Directory, Personal Records as Historical Sources